2012
DOI: 10.1007/s12020-012-9631-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of Gallium-68 somatostatin receptor PET and PET/CT in patients with thoracic and gastroenteropancreatic neuroendocrine tumours: a meta-analysis

Abstract: Sixteen studies comprising 567 patients were included in this meta-analysis. The pooled sensitivity and specificity of SMSR PET or PET/CT in detecting NETs were 93% (95% confidence interval [95% CI]: 91-95%) and 91% (95% CI: 82-97%), respectively, on a per patient-based analysis. The area under the ROC curve was 0.96. In patients with suspicious thoracic and/or GEP NETs, SMSR PET and PET/CT demonstrated high sensitivity and specificity. These accurate techniques should be considered as first-line diagnostic im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
149
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 244 publications
(160 citation statements)
references
References 29 publications
5
149
0
6
Order By: Relevance
“…Somatostatin receptor PET/CT is increasingly used in patients with known or suspected neuroendocrine tumours demonstrating high diagnostic accuracy and is superior compared to 111 In-pentetreotide scintigraphy in this setting [6,7]. Recent articles in the literature assessed the diagnostic accuracy of somatostatin receptor PET/CT using different somatostatin analogues labelled with 68 Ga ( 68 Ga-DOTATATE, 68 Ga-DOTANOC and 68 Ga-DOTATOC) in patients with extraadrenal PGL [8][9][10][11][12][13][14][15][16][17], based on the increased expression of somatostatin receptors in PGL neoplastic cells [18].…”
mentioning
confidence: 99%
“…Somatostatin receptor PET/CT is increasingly used in patients with known or suspected neuroendocrine tumours demonstrating high diagnostic accuracy and is superior compared to 111 In-pentetreotide scintigraphy in this setting [6,7]. Recent articles in the literature assessed the diagnostic accuracy of somatostatin receptor PET/CT using different somatostatin analogues labelled with 68 Ga ( 68 Ga-DOTATATE, 68 Ga-DOTANOC and 68 Ga-DOTATOC) in patients with extraadrenal PGL [8][9][10][11][12][13][14][15][16][17], based on the increased expression of somatostatin receptors in PGL neoplastic cells [18].…”
mentioning
confidence: 99%
“…Recently, PET/CT using somatostatin analogues (such as DOTANOC, DOTATOC, DOTATATE) labelled with 68 Ga has been increasingly used in patients with BCs due to its high diagnostic accuracy in NET detection [10]. Some false-negative results of somatostatin receptor PET/CT in pulmonary NETs may be due to tumours with low expression of somatostatin receptors.…”
mentioning
confidence: 99%
“…Some false-negative results of somatostatin receptor PET/CT in pulmonary NETs may be due to tumours with low expression of somatostatin receptors. Conversely, inflammatory lesions may occasionally cause false-positive results due to the high expression of somatostatin receptors on the cell surface of the inflammatory cells [10]. Somatostatin receptor PET/CT has been demonstrated to be superior compared to somatostatin receptor scintigraphy in evaluating lung NETs, due to the superior spatial resolution of PET imaging [6].…”
mentioning
confidence: 99%
“…On the other hand, recent studies demonstrated that Ga-68-somatostatin analogue PET/CT is an accurate functional imaging method in patients with neuroendocrine tumours [5], including those with head and neck paraganglioma [6]. This imaging technique non-invasively provides data on receptor expression on neuroendocrine tumour cells with direct therapeutic implications, identifying those patients who are eligible for a treatment with somatostatin analogues.…”
mentioning
confidence: 99%